Mitigation of Inpatient Standard Class Risk at Hospital X - Sophie Aileen; Sutopo Patria Jati; Cahya Tri Purnami (Green Publisher Indonesia, 2024)
Background: The Standard Inpatient Class Policy (KRIS) in Indonesia aims to provide equitable healthcare services, ensuring the same standards in inpatient wards across all hospitals in Indonesia. This policy has been issued since 2021 and is mandatory for all hospitals to implement by December 2024. The implementation of the KRIS policy impacts hospitals, necessitating analysis and mitigation of risks arising from its implementation. This study aims to provide an overview of the analysis and mitigation of risks in the standard inpatient class implemented by Hospital X. Method: Qualitative research using Focus Group Discussions (FGDs) in November 2023 involving 7 key informants, including Hospital Directors and Department Heads, regarding the mitigation of risks in the standard inpatient class using risk analysis matrices. Results: There are two criteria for the standard inpatient class that pose a very high level of risk, namely the building components lacking high porosity and the density of ward spaces and bed spacing. Conclusion: Hospital X implements risk mitigation by taking actions to reduce the impact of risks through room improvement based on related room reports, risk reduction mitigation by planning inpatient building renovations, and risk acceptance mitigation by allowing ward areas to be 9.8 square meters per bed.